Received Wisdom: The Use of Authority in Medieval Islamic Philosophy. (May 2021) - Adamson, Peter
Abstract: In this paper I challenge the notion that medieval philosophy was characterized by strict adherence to authority. In particular, I argue that to the contrary, self-consciously critical reflection on authority was a widespread intellectual virtue in the Islamic world. The contrary vice, called 'taqlīd', was considered appropriate only for those outside the scholarly elite. I further suggest that this idea was originally developed in the context of Islamic law and was then passed on to authors who worked within the philosophical tradition.